DESCRIPTION OF ATTITUDE OF COUPLES OF REPRODUCTIVE AGE REGARDING SELECTED EFFECTIVE CONTRACEPTION METHODS AT BANGUNSARI HEALTH CENTER - Mufida Dian Hardika; Lilis Suryani (Sean Institute, 2022)
Family Planning (KB) is a way to set the interval between pregnancies and determine the number of children in the family. The research problem is that there are still many couples of childbearing age (PUS) choosing effective contraception at the Bangunsari Health Center, Dolopo District, Madiun Regency, so this study aims to describe the attitude of the Couples of Reproductive Age about the chosen effective contraceptive method at the Bangunsari Health Center. This research uses descriptive research type. The study population was 144 people of childbearing age couples who had not participated in family planning at the Bangunsari Health Center, Dolopo District, Madiun Regency. The sample of the research was 72 women who had not participated in family planning at the Bangunsari Health Center in Madiun district. Sampling using random sampling, research design using cross sectional. Data collection was carried out by means of a questionnaire. Data analysis using frequency distribution. The results of the study identified that the majority of respondents had a neutral attitude about the chosen effective contraceptive method, namely 35 respondents (48%) and a small number of respondents had a negative attitude about the selected effective contraceptive method, namely 13 respondents (18%). he conclusion of the study is that the majority of respondents have a neutral attitude about the effective contraceptive methods they have chosen. It is hoped that this will be able to provide counseling to the public, especially couples of childbearing age regarding the benefits of using selected effective contraceptive methods so that acceptors no longer need to feel afraid if they want to use family planning.